ANALYSIS OF RISK FACTORS AND PREVALENCE OF NON-COMMUNICABLE DISEASES (NCDS) IN INDONESIAN MIGRANT WORKERS: A SYSTEMATIC REVIEW - Tri Aan Agustiansyah; Imran Zamzami; Benedikta Mardewi Iswari; Rafita Ofti Sepilena; Supriadi; Imran; Suriadi Jais (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Background: Indonesian Migrant Workers (PMI) are a vulnerable population group facing multiple health risks due to heavy workloads, environmental stress, and limited access to healthcare services in their host countries. Although numerous individual studies have been conducted, a comprehensive synthesis of the burden of disease in this population is still limited. This study aims to systematically review the prevalence and risk factors of disease in PMI over the past decade. Methods: This systematic review was conducted following the PRISMA ( Preferred Reporting Items for Systematic Reviews and Meta-Analyses ) guidelines. A literature search was conducted in PubMed, ScienceDirect, and Google Scholar databases for articles published between 2016 and 2026. Inclusion criteria included quantitative and mixed-methods studies focusing on the health conditions of PMI in various destination countries (such as Malaysia, Taiwan, and Hong Kong). Study quality assessment was conducted using the Joanna Briggs Institute (JBI) instrument. Results: A total of 25 articles met the inclusion criteria for analysis. The review results indicate that non-communicable diseases (NCDs) such as hypertension, type 2 diabetes mellitus, and musculoskeletal disorders have a significant prevalence among migrant workers in the domestic and construction sectors. In addition to physical health, mental health disorders such as depression and anxiety were found to be closely associated with social isolation and long work duration. Key risk factors identified include a sedentary lifestyle, uncontrolled diet in the host country, and structural barriers such as language barriers and legal status in accessing professional health services. Conclusion: This review confirms a decline in the health conditions of migrant workers as the duration of their placement increases. More integrative health protection policies are needed, ranging from preventive education before departure to the provision of inclusive health services in the host country to reduce morbidity rates among migrant workers.